Treatment choices and outcomes of patients with manometrically diagnosed achalasia. Issue 5 (23rd March 2015) - Yeung, J. C.; Finley, C.; Hanna, W. C.; Miller, L.; Ferri, L.; Urbach, D. R.; Darling, G. E.
Summary: This prospective population‐based study was designed to evaluate treatment choices in patients with new manometrically diagnosed achalasia and their outcomes. Patients referred to the esophageal function laboratory were enrolled after a new manometric diagnosis of achalasia. Patients completed an initial achalasia symptom score validated questionnaire on their symptom severity, duration, treatment pre‐diagnosis and Medical Outcomes Study 36‐item Short‐Form (SF‐36) survey. Treatment decisions were made by the referring physician and the patient. Follow‐up questionnaires were completed every 3 months for 1 year. Patients who chose not to undergo treatment at 1‐year follow‐up completed another questionnaire after 5 years. Between January 2004 and January 2005, 83 of 124 eligible patients were enrolled. Heller myotomy was performed on 31 patients, three patients received botulinum toxin injections, and 25 patients received 29 pneumatic balloon dilatations. Twenty‐four patients chose to receive no treatment. Following treatment, patients treated with surgery, dilatation and botulinum toxin had an average improvement in achalasia symptom score of 23 +/− 12.2, 17 +/− 10.9, and 9 +/− 14, respectively. Patients receiving no treatment had worsening symptoms with a symptom score change of −3.5 +/− 11.4. Surgery and dilatation resulted in significant improvement ( P < 0.01) relative to no treatment. In univariate logistic regression, symptom severity score (odds ratio [OR] 1.04, 95% confidence interval [CI] 1.00 to 1.08), sphincter tone (OR 1.04, 95% CI 1.00 to 1.09), difficulty swallowing liquids (OR 3.21, 95% 1.15 to 8.99), waking from sleep (OR 2.75, 95% 1.00 to 7.61), and weight loss (OR 5.99, 95% CI 1.93 to 18.58) were all significant in predicting that patients would select treatment. In the multivariate analysis, older age (OR 1.05, 95% CI 1.01 to 1.09) and weight loss (OR 3.91, 95% CI 1.02 to 15.2) were statistically significant for undergoing treatment. At 5 years, five (21%) of those who had initially declined treatment at 1 year ultimately chose a treatment. Patients who finally chose Heller myotomy had lower mental component dimension scores on the SF‐36 at 1 year than those who did not. This study shows that almost one third of patients with manometrically diagnosed achalasia choose not to undergo treatment within 1 year of their diagnosis. Patients who are more symptomatic appear to be more likely to undergo treatment by univariate analysis. In multivariate analysis, increasing age and weight loss are predictive of those who will undergo treatment, with weight loss having the greatest influence. Patients who choose not to undergo treatment make lifestyle changes to maintain their quality of life, and only a minority of them ultimately undergo treatment.